The search for machanism of genetic abberation in the infronic regions of the uridine-diphospate glucuronosyl transferase 1a1 (ugt1a1) gene among neonatal jaundice Malay infants without mutations in the promoter and exonic regions - Yusoff, Surini (Pusat Pengajian Kesihatan, 2015)
Many studies have been focusing on the exonic regions of the uridine diphosphate g/ucuronosy/transferase 1 A 1 (UGT1A1) gene in determining the risk factors of neonatal jaundice. However, very few studies suggested the intronic region as a part of it. This study was conducted to determine the possibility of involvement of polymorphisms in the intronic regions among neonatal jaundice Malay infants without polymorphism in the exons. The rationale of this study lwas rely on the other possible risk factors since there were still many infants developed jaundice without exhibit any polymorph isms in the exons of the UGT1A 1 gene. High resolution melting analysis has been used to screen for our target polymorphisms and confirmed by sequencing analysis. A total of 510 (n=260 samples of non-hyperbilirubinemia infants and 250 samples of hyperbilirubinemia infants) were evaluated. This study revealed that from six mutations in the promoter region evaluated,only c.-3279T>G was associated with neonatal jaundice and was statistically significant. Other polymorph isms were detected in the intronic regions such as IVS2+15(T>C) and IVS2+18(C> T) in non· hyperbilirubinemia group while IVS2+82 (C> T) was identified in hyperbilirubinemia group. However, no significanl association Therefore, so far only the c.-3279T>G is a possible risk factor of neonatal jaundice in Malay population.